Microglial Modulation in Alzheimer’s Disease: Central Players in Neuroinflammation and Pathogenesis - Hussain, Md Sadique; Khan, Yumna; Fatima, Rabab; Maqbool, Mudasir; Ramalingam, Prasanna Srinivasan; Khan, Mohammad Gayoor; Bisht, Ajay Singh (Current Alzheimer Research, 2025)
Alzheimer’s disease (AD) is an age-related, progressive neurodegenerative disorder of cognition with clinical features and anatomical hallmarks of amyloid-β plaques and/or neurofibrillary tangles. New studies revealed that microglia, the native immune cells in the brain, are crucial in the development of AD. The present review aims at outlining various roles of microglia in AD especially targeting their role in neuroinflammation. These indicate that microglial dysfunction contributes to AD pathology by affecting both amyloid-β phagocytosis and tau hyperphosphorylation. Other investigative molecular perpetrators, including TREM2, also influence the microglial relevance to amyloid and tau, as well as the overall disease phase. The functional microglia can protect neurons, while the dysfunctional one has the capability of derailing neuronal potentials and aggravating neurodegeneration. We have also discussed therapeutic strategies that start with targeting microglia to reduce neuroinflammation and reinstate balance. However, certain problems, including the side effects of microglial modulation, cost constraint, and accessibility, are areas of concern. In this review, the author presents the current state of knowledge on the potential of microglia-targeted treatments, their risks, and benefits. Thus, this article emphasizes the importance of the expansion of research to decipher the exact manipulation of microglia in AD with the goal of applying these findings given therapeutic approaches.
Keywords: TREM2